Evaluation of probiotics ability to enhance population density, growth rate, and neonates production of Moina micrura in different environmental parameters - Sofea, Nur Amiratul; Samat, Nur Amalina; Syukri, Muhammad Fadhil; Rasdi, Wan Nadiah (Universiti Putra Malaysia, 2024)
Salinity, light intensity, and oxygen concentration are key environmental factors that significantly affect biological processes and the composition and dispersion of Moina biomass. Evaluating the effectiveness of probiotic enrichment in improving population density, growth rate, and neonate production can provide valuable details on the effectiveness of probiotics in enhancing the resilience and viability of Moina micrura under suboptimal circumstances. The purpose of this research project is to assess the efficacy of two probiotics, Bacillus pocheonensis strain S2 and Lysinibacillus fusiformis strain A1, in improving the population density, growth rate, and reproductive output in M. micrura across various environmental conditions. Moina micrura were treated with each probiotic at a volume of 5 x 105 CFU/ml under different levels of salinity (0, 2, 4, and 6 ppt), light intensity (800, 1,000, 1,500, and 2,000 lux), and oxygen concentration (80, 70, 60, and 50%). The results indicated that M. micrura treated with L. fusiformis A1 at 0 ppt attained the highest population density (6 ± 0.90 Ind./ml), growth rate (0.355 ± 0.030 µ), and number of offspring production (5 ± 0.75 Ind./ml). The highest point of population density (5 ± 0.07 Ind./ml), growth rate (0.381 ± 0.002 µ) and number of offspring (7 ± 0.41 Ind./ml) of M. micrura were obtained while treated with B. pocheonensis S2 at light intensity of 1,500 lux. Similarly, the highest population density (5 ± 0.60 Ind./ml), growth rate (0.365 ± 0.190 µ), and offspring production (2 ± 0.25 Ind./ml) of M. micrura were observed during enrichment with B. pocheonensis S2 at 70% oxygen concentration. Therefore, these results suggested that the optimum conditions for enriching M. micrura with B. pocheonensis S2 are salinity of 0 ppt, 70% oxygen concentration, and a light intensity level of 1,500 lux.